The relationship between ambient temperature and match running performance of elite soccer players - Morgans, Ryland (2023)
The influence of environmental factors on key physical parameters of soccer players during competitive match-play have been widely investigated in the literature, although little is known on the effects of sub-zero ambient temperatures on the performance of adult elite soccer players during competitive matches. The aim of this study was to assess how the teams’ match running performance indicators are related to low ambient temperature during competitive matches in the Russian Premier League. A total of 1142 matches played during the 2016/2017 to 2020/2021 seasons were examined. Linear mixed models were used to assess the relationships between changes in ambient temperature at the start of the match and changes in selected team physical performance variables, including total, running (4.0 to 5.5 m/s), high-speed running (5.5 to 7.0 m/s) and sprint (> 7.0 m/s) distances covered. The total, running and high-speed running distances showed no significant differences across temperatures up to 10˚C, while these showed small to large decreases at 11 to 20˚C and especially in the >20˚C ranges. On the contrary, sprint distance was significantly lower at temperature of -5˚C or less compared to higher temperature ranges. At sub-zero temper atures, every 1˚C lower reduced team sprint distance by 19.2 m (about 1.6%). The present findings show that a low ambient temperature is negatively related to physical match perfor mance behavior of elite soccer players, notably associated with a reduced total sprint distance.